2015
DOI: 10.12714/egejfas.2014.31.2.05
|View full text |Cite
|
Sign up to set email alerts
|

Structural characteristics of towed fishing gears used in the Samsun Coast (Black Sea)

Abstract: Abstract:In this study, structural characteristics of towed fishing gears (bottom and beam trawls) used on the coasts of Samsun were investigated as part of EU-FP7 BENTHIS project. Data for bottom and beam trawl (net, otter board, beam etc.) were obtained in situ investigations and survey studies with fishermen face to face. The numbers of total and active trawl vessel in this area were determined after that these vessels were classified according to size categories. Stratified subsampling for representing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The gear weighed around 90 kg excluding the weight of the mesh. Steel wires of 5 mm in width present on the frames of the beam trawls provided ground contact to reveal the whelks and to facilitate dragging of the net (Kaykaç et al, 2014). Both ends of the steel wires were http://epublishing.ekt.gr | e-Publisher: EKT | Downloaded at 10/07/2020 23:17:02 | mounted tightly to the feet of the frame (5 cm in depth and 5 mm thickness, Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gear weighed around 90 kg excluding the weight of the mesh. Steel wires of 5 mm in width present on the frames of the beam trawls provided ground contact to reveal the whelks and to facilitate dragging of the net (Kaykaç et al, 2014). Both ends of the steel wires were http://epublishing.ekt.gr | e-Publisher: EKT | Downloaded at 10/07/2020 23:17:02 | mounted tightly to the feet of the frame (5 cm in depth and 5 mm thickness, Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Traditional beam trawls (locally known as algarna) are the preferred capture device for this species due to comparatively higher catch efficiency (Altınağaç et al, 2004). Referred to as dredge by some authors (Çelik and Samsun, 1996;Altınağaç et al, 2004;Sağlam et al, 2008) and as beam trawl by others (Kaykaç et al, 2014;Zengin et al, 2014), the algarna better resembles a beam trawl in terms of net design, technical specifications, and operational functions, albeit shorter than conventional beam trawls (Valdermarsen and Suuronen, 2003). The studies in the south-eastern Black Sea have shown that this gear causes damage to small benthic organisms since the diamond mesh openings are clogged by veined rapa whelks during the tow (Sağlam et al, 2008;Eryaşar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In the veined rapa whelk fishery, traditional beam trawl method (locally known as algarna) is preferred because of its high efficiency (Altınağaç et al 2004). Algarna is operated with beam trawl technique (Kaykaç et al 2014) but it is smaller than beam trawl that is normally used. For this fishery, target species is only the veined rapa whelk and other species like fish and crab are thrown back into the sea as dead or alive and small ones like bivalves are packed with the target species without any elimination (Eryaşar et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These are more environmentally friendly fishing gears with low ecosystem impact index because they are aimed at the target species and cause minimum damage to the ground (16,17). There are limited studies on beam trawls, the most effective means of fishing for the species (10,18,19). There is an urgent need to make structural changes to the beam trawls and to reduce the benthic effect when it is considered that the average annual production in the last 10 years was about 10,000 t and 90% of the production was provided by this fishing gear.…”
Section: Introductionmentioning
confidence: 99%